2015
DOI: 10.1111/eea.12306
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of habitat type to residency and dispersal choices by overwintered and summer adult Colorado potato beetles

Abstract: The walking and flight dispersal of marked overwintered and summer Colorado potato beetles (CPB), Leptinotarsa decemlineata (Say) (Coleoptera: Chrysomelidae), released in field box‐plots was monitored simultaneously in six habitats over a period of 4 days. The emigration out of plots by walking beetles was calculated from the catch in linear pitfall traps completely surrounding each box‐plot and emigration flight was estimated from the number of beetles missing from the plot or captured by the trap. Overwinter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Each model contained the release habitat (pepper or trap crop), sampling period (flowering, fruiting, or post‐harvest), and sex (male or female) as explanatory variables, and release date as a random blocking variable to control for abiotic variables. The second‐order interaction between sampling period and release habitat was also included on the basis that different habitats have varying retention capacities (e.g., Boiteau & Mackinley, ), and that phenology of crops often impacts the abundance of H. halys (Martinson et al., ). In addition, the model examining distance moved also contained the time since release (1, 3, 6, or 24 h after release) as an additional explanatory variable.…”
Section: Methodsmentioning
confidence: 99%
“…Each model contained the release habitat (pepper or trap crop), sampling period (flowering, fruiting, or post‐harvest), and sex (male or female) as explanatory variables, and release date as a random blocking variable to control for abiotic variables. The second‐order interaction between sampling period and release habitat was also included on the basis that different habitats have varying retention capacities (e.g., Boiteau & Mackinley, ), and that phenology of crops often impacts the abundance of H. halys (Martinson et al., ). In addition, the model examining distance moved also contained the time since release (1, 3, 6, or 24 h after release) as an additional explanatory variable.…”
Section: Methodsmentioning
confidence: 99%
“…In the spring, beetles emerge from overwintering sites in the soil, and typically walk, rather than fly, in search of the nearest potato crop, orienting by olfactory cues (Boiteau, Alyokhin, & Ferro, 2003). Greater distances between potato fields together with unfavorable composition of the intervening landscape can impede navigation of CPB and make it difficult for CPB to reach a potato field; for example, water bodies, cereal crops, and grassland present barriers to CPB movement (Boiteau & MacKinley, 2015Huseth et al, 2012;Lashomb & Ng, 1984). On the other hand, because potato attracts and retains CPB, areas with sparse potato land cover could unexpectedly enhance connectivity, because successful migrants must travel farther than beetles from areas with dense potato land cover.…”
mentioning
confidence: 99%
“…The temperature and light conditions during the laboratory trials were not conducive to beetle flight. Outdoors, Boiteau and MacKinley (2015) found that of more than 80% of Colorado potato beetles released on a platform in the middle of a water surface had abandoned it after 96 hours, with 64% flying off (rather than swimming off), demonstrating that flight can play an important role in improving their survival once drifting beetles have encountered driftwood or other floating debris.…”
Section: Discussionmentioning
confidence: 99%
“…This near water density combined to the hydrophobic cuticle makes the beetle very buoyant. Supported by the water surface tension, these floating beetles can easily be dispersed by wind as observed by Boiteau and MacKinley (2015) in water-filled outdoor box plots. Adding soap to the water of some of our test bottles removed the water surface tension and beetles immediately sank just below the water surface.…”
Section: Survival At the Surface Of Fresh And Salt Watermentioning
confidence: 96%
See 1 more Smart Citation